TREN THRIFTING DI PASAR KRENENG DITINJAU DARI PERSPEKTIF SOSIOLOGI WAKTU LUANG - Tanjung, Mario Adinata; Suryani, Ni Gusti Ayu Putu; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
This research focuses on the phenomenon of leisure activities that are used for Thrifting at the Kreneng Market, North Denpasar. The purpose of this study is to analyze thrift activities as an option for the use of leisure time used by the community. The method used in this study is a qualitative approach. The theory used as a scalpel in this study is John Wilson's theory of leisure sociology. Through the sociology of leisure theory approach, the author wants to explore the choice of a person's leisure activities related to work, family, social stratification, and life cycles. The results of the study show that thrifting activities are an alternative to leisure recreation for a person who has a relationship with several aspects such as work, family, life cycle, and social stratification. In some job sectors, leisure time is not available for workers, so they tend to look for entertainment or fun activities after work. The choice of recreational activities is often influenced by collective decisions within the family, and the implementation of recreation together has been proven to have a positive impact on the harmony and well-being of family members. Furthermore, the life cycle affects a person's choice of activities, how are the current fashion trends that are an attraction for teenagers to continue to look attractive and contemporary. Social stratification is also reflected in thrifting activities, which can be seen from the number of clothes purchased and consumer orientation towards products, especially those from well-known brands. The last thing that needs to be considered again for sellers and visitors is to maintain the cleanliness of the environment at Kreneng Market as well as the cleanliness and sterility of the clothes purchased to avoid germs and other diseases. A clean environment will create a professional impression and make visitors feel comfortable and a clean market will reflect the government's seriousness in fostering a sustainable economy.